Method fragments for agent design methodologies: from standardisation to research. (19th April 2007) - Cossentino, Massimo; Gaglio, Salvatore; Garro, Alfredo; Seidita, Valeria
The method engineering paradigm enables designers to reuse portions of design processes (called method fragments or chunks in literature) to build processes that are expressly tailored for realising a system that is specific for some problem or development context. This paper initially reports on the standardisation attempt carried out by the FIPA Methodology Technical Committee (TC) and then presents the research activities we did starting from that work; these resulted in a slightly different definition of some of the most important elements of the approach in order to support a multiview representation of the fragment (the views are process, reuse, storing and implementation). The paper also describes the documents we used for representing a fragment and concludes with an example.